Pengaruh Eco Efficiency, Corporate Social Responsibility dan Accrual Quality Terhadap Nilai Perusahaan - Gine Das Prena; Putu Purnama Dewi; Ketut Tanti Kustina; IGA Agung Omika Dewi; I Nengah Wirsa (Universitas Matana, 2019)
This study aims to determine the influence of Eco-Efficiency, Corporate Social Responsibility, and Accrual Quality on Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2018 The sample selection uses a purpose sampling which is as many as 100 samples of manufacturing companies. To measure the hypothesis is done by t test and test f. The data analysis technique used in this study is the classic assumption test and multiple linear regression test.In addition, all variables are declared free of interference from existing classical assumptions. From the results of multiple linear regression tests the results of the test f obtained a significant value of 0.000 or <0.05. This means that Eco-Efficiency, Corporate Social Responsibility and Accrual quality in Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2018 have a significant simultaneous effect. Partial testing shows the results that all independent variables significantly influence the value of the company